(untitled) (Bangladesh Medical Journal Khulna, 2019)
Background: Liver abscesses, both amoebic and pyogenic, continue to be an important cause of morbidity and mortality in tropical country. Traditionally for many years they were treated with antimicrobial alone, blind percutaneous aspiration or surgical exploration. This conception gradually changes into guided percutaneous aspiration or drainage with development of advanced diagnostic imaging modality. Objectives: To evaluate the safety and efficacy of management of liver abscess by Ultrasound (US) guided percutaneous needle aspiration. Methods: From August 2009 to July 2018 a total 380 patients with liver abscess were referred to the department of radiology and imaging for US guided percutancous aspiration. All patients were evaluated clinically and by USG. Aspiration of the abscess was carried out under strict aseptic precaution. Results: A total of 380 patients with liver abscess were successfully treated, consisting of 338 males and 42 females, male female ratio 8:1. The age ranges from 11 to 80 years. Majority (78%) had single abscess and 22% had two or more. Most of the abscess are located in the right lobe of liver (79%). Single needle aspiration were needed in 30% of patient, second aspiration were needed in 38% of patients and third aspiration in 32% of patients. Average aspiration per patient was 2.02. The amount of aspirated pus ranged from 250 to 2450 ml. Conclusion: Ultrasound guided percutaneous needle aspiration of liver abscess is a safe and successful therapeutic approach in the treatment of liver abscess whether pyogenic or amoebic. Bang Med J (Khulna) 2018; 51 : 3-6